2022
DOI: 10.4103/ijdr.ijdr_331_22
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Sense of Coherence, OHRQoL, and Dental Caries among Nursing Students in South India

Abstract: Background: Dental caries is one of the most common dental diseases that affect all population and is associated with the avoidance of care. Research has reported that sense of coherence (SOC) is related to many aspects of health including oral health. SOC determines the quality of health and might have a direct association with the development of subjective assessments of oral health. Objectives: To find the association between SOC, Oral Health-Related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…According to systematic reviews, individuals with a strong SOC are more likely to report more favourable oral health-related behaviours, such as less sugar consumption, more frequent toothbrushing, regular dental attendance [ 17 ] and having a clinical oral status with less dental caries [ 18 – 20 ] and periodontal disease [ 20 , 21 ]. SOC has also been found to be associated with oral health-related quality of life [ 22 , 23 ]. A study among adults and elderly individuals in Brazil found that individuals with a strong SOC were more likely to not have any oral or tooth-related impact on daily performance compared to individuals with a weak SOC [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to systematic reviews, individuals with a strong SOC are more likely to report more favourable oral health-related behaviours, such as less sugar consumption, more frequent toothbrushing, regular dental attendance [ 17 ] and having a clinical oral status with less dental caries [ 18 – 20 ] and periodontal disease [ 20 , 21 ]. SOC has also been found to be associated with oral health-related quality of life [ 22 , 23 ]. A study among adults and elderly individuals in Brazil found that individuals with a strong SOC were more likely to not have any oral or tooth-related impact on daily performance compared to individuals with a weak SOC [ 24 ].…”
Section: Introductionmentioning
confidence: 99%